2009
DOI: 10.1186/1471-2474-10-140
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the ProFHER (PROximal Fracture of the Humerus: Evaluation by Randomisation) trial: a pragmatic multi-centre randomised controlled trial of surgical versus non-surgical treatment for proximal fracture of the humerus in adults

Abstract: BackgroundProximal humeral fractures, which occur mainly in older adults, account for approximately 4 to 5% of all fractures. Approximately 40% of these fractures are displaced fractures involving the surgical neck. Management of this group of fractures is often challenging and the outcome is frequently unsatisfactory. In particular it is not clear whether surgery gives better outcomes than non-surgical management. Currently there is much variation in the use of surgery and a lack of good quality evidence to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 20 publications
(25 reference statements)
0
41
0
2
Order By: Relevance
“…40 The choice of surgical intervention was the decision of the surgeons, who had to use techniques with which they were experienced and fully familiar. Good standards of non-surgical care, including care-provider competence, and a comparable provision of rehabilitation for both groups of patients were expected.…”
Section: Summary Of Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…40 The choice of surgical intervention was the decision of the surgeons, who had to use techniques with which they were experienced and fully familiar. Good standards of non-surgical care, including care-provider competence, and a comparable provision of rehabilitation for both groups of patients were expected.…”
Section: Summary Of Trial Designmentioning
confidence: 99%
“…The final version of the study protocol (version 7), shown in Appendix 3, was published in 2009. 40 Appendix 4 summarises the changes to the protocol.…”
Section: Summary Of Trial Designmentioning
confidence: 99%
“…2,3 Non-operative treatment is the gold standard for undisplaced proximal humerus fractures, with good outcomes. 4,5 Displaced fractures may be treated operatively using different fixation techniques which include percutaneous k-wire fixation, proximal humerus locking plate (LP) and screw fixation, intramedullary nailing (IMN), hemiarthroplasty with different success rates. 2 Open reduction and internal fixation (ORIF) and plate osteosynthesis and closed reduction with nailing are two common methods of fixing Neer 6 two-part proximal humerus fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Given the established lack of evidence to conclude whether surgical intervention produces consistently better outcomes than non-surgical treatment for these fractures 5 , the Proximal Fracture of the Humerus Evaluation by Randomisation (PROFHER) trial was conducted to evaluate the clinical effectiveness and cost-effectiveness of surgery compared with nonsurgical treatment of the majority of displaced fractures of the proximal humerus involving the surgical neck in adults 6 .…”
Section: Introductionmentioning
confidence: 99%